Point-of-care tests for syphilis and yaws in a low-income setting - A qualitative study of healthcare worker and patient experiences. - Michael Marks; Tommy Esau; Rowena Asugeni; Relmah Harrington; Jason Diau; Hilary Toloka; James Asugeni; Eimhin Ansbro; Anthony W Solomon; David Maclaren; Michelle Redman-Maclaren; David C W Mabey (Public Library of Science (PLoS), 2018)
The human treponematoses comprise venereal syphilis and the three non-venereal or endemic treponematoses yaws, bejel, and pinta. Serological assays remain the most common diagnostic method for all treponemal infections. Point-of-care tests (POCTs) for syphilis and yaws allow testing without further development of infrastructure in populations where routine laboratory facilities are not available. Alongside the test's performance characteristics assessed through diagnostic evaluation, it is important to consider broader issues when rolling out a POCT. Experience with malaria POCT roll-out in sub-Saharan Africa has demonstrated that both healthcare worker and patient beliefs may play a major role in shaping the real-world use of POCTs. We conducted a qualitative study evaluating healthcare worker and patient perceptions of using a syphilis/yaws POCT in clinics in the East Malaita region of Malaita province in the Solomon Islands. Prior to the study serology was only routinely available at the local district hospital.The POCT was deployed in the outpatient and ante-natal departments of a district hospital and four rural health clinics served by the hospital. Each site was provided with training and an SOP on the performance, interpretation and recording of results. Treatment for those testing positive was provided, in line with Solomon Islands Ministry of Health and Medical Services' guidelines for syphilis and yaws respectively. Alongside the implementation of the POCT we facilitated semi-structured interviews with both nurses and patients to explore individuals' experiences and beliefs in relation to use of the POCT.Four main themes emerged in the interviews: 1) training and ease of performing the test; 2) time taken and ability to fit the test into a clinical workflow; 3) perceived reliability and trustworthiness of the test; and 4) level of the health care system the test was most usefully deployed. Many healthcare workers related their experience with the POCT to their experience using similar tests for malaria. Although the test was considered to take a relatively long time to perform the benefits of improved access to testing were considered positive by most healthcare workers. Qualitative data is needed to help inform better training packages to support the implementation of POCT in low-resource settings.